Oral Administration of Alginate From A Tropical Brown Seaweed, Sargassum sp. To Enhance Non-Spesific Defense In Walking Catfish (Clarias sp.) - Isnansetyo, Alim; Irpani, Husni Mubarok; Wulansari, Tyas Ayu; Kasanah, Noer (Aquacultura Indonesiana, 2014)
Alginate that is usually extracted from brown seaweeds, is a bioactive substance with immunomodulator activity. The purpose of this research was to evaluate the effect of oral administration of alginate on the non-specific immune system of walking catfish (Clarias sp.). An experiment was conducted in a Completely Randomized Design with five treatments in triplicates. Alginate was supplemented in feed at doses of 0 (control treatment), 2, 4, 6 and 8 g/kg of feed. The walking catfish was fed twice daily at feeding rate of 5%. Non-specific defense parameters evaluated were Nitroblue Tetrazolium (NBT) activity, phagocytic activity (PA), phagocytic index (PI), leukocyte differentiation, hematocrit and leucocrit. The parameters were observed prior to be treated, 5th, 10th and 15th days after treatments. Oral administration of alginate at 4 g/kg of feed increased NBT and PA activities significantly (P<0.05) in 5 days, while alginate at a dose of 6 g/kg increased NBT activity and monocyte percentage significantly (P<0.05) in 5 days. These results suggested that oral administration of alginate at 4 g/kg effectively increased non-specific immune system of walking catfish.